Analysis of the Implementation of Total Quality Management and Organizational Commitment in Improving the Performance of Education Personnel at Semarang State University - Suprapti Suprapti; Lesa Paranti; Margunani Margunani; Evita Septiana Tyas Utami (Universitas Negeri Semarang, 2023)
The purpose of this study is to develop a strategy for implementing TQM in improving the performance of teaching staff at Semarang State University that is inclusive. This research is a quantitative and qualitative descriptive research. Quantitative descriptive research is a research that consists of problem formulation, constructing a model, collecting data, analyzing the results, and implementing it The analytical method used in this research is Interpretative Structural Modeling (ISM) analysis. ISM as applied by Bhattacharya and Momaya (2009), is a sophisticated interactive planning methodology that allows a group of people, working as a team, to develop a structure that defines the relationships among the elements in a set. The results of the classification of the elements of the strategy for developing the competence and expertise of educational staff in supporting the acceleration of UNNES to become PTN-BH which consists of 15 criteria produce 8 levels of policy. The policy element of tightening selection in the recruitment of educational staff (A1) and the element of assistance in increasing competence (A3) are at the first level. Classification of elements of the competency improvement policy for educational staff at UNNES can be classified into 4 (four) sectors. The sector occupied by the most elements is sector III (Linkage). The elements in this sector have a large driving force but also have a large dependence on other elements.